Strategic Communication and Religious Tolerance in Multicultural Societies: A Bibliometric Review from Scopus Database - Mu'min Syaifuddin; Toto Sugito; Meria Octavianti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Religious tolerance is essential for sustaining social cohesion in multicultural societies shaped by globalization and digital communication. Strategic communication contributes to inclusive narratives and interfaith understanding, yet research integrating these domains remains fragmented. This study systematically maps the intellectual structure, research trends, and gaps in strategic communication and religious tolerance scholarship using a bibliometric approach. A descriptive quantitative analysis examined 290 Scopus-indexed publications published between 1985 and 2025. Citation analysis, co-authorship mapping, and keyword co-occurrence were applied to identify dominant themes, influential contributors, and knowledge structures. The findings indicate a highly centralized research landscape dominated by Western countries, particularly the United States and Australia. Public relations emerges as the principal conceptual framework linking organizational, community, and institutional communication, while religious tolerance is often treated implicitly rather than as a core analytical concept. The study reveals limited representation of non-Western contexts, highlighting a significant research gap and opportunities for more inclusive).